Designing an Emergency Panic Buttons as A Safety Support System for Solitary Elder - Muhammad Navis Mirza; Iqbal Faza; Iwan Prasetyo (Yayasan Adra Karima Hubbi, 2024)
Background. According to Presidential Regulation No. 88 of 2021 on the National Strategy for the Elderly, elderly individuals are those aged 60 and above. Solitary elderly individuals face various complex issues, including limited social support, mobility restrictions, healthcare neglect, safety risks, and insufficient access to information and technology. In 2021, 6.75% of Kudus Regency's population was elderly, with a 0.72% increase from 2018 to 2021. Notably, two solitary elderly individuals were found deceased in 2023. Purpose. This research focuses on designing an emergency panic button system to enhance the safety of solitary elderly individuals. The study aims to ensure their safety and security, particularly during health emergencies. Method. The research involves developing a user-friendly panic button system, assessing its usability and reliability, and evaluating its impact on elderly safety. Results. The results indicate that the emergency panic button significantly improves response times in emergencies, providing a crucial support system for solitary elderly individuals. Conclusion. This innovation has broader implications for advancing health and safety technologies in Indonesia and could serve as a model for similar solutions in other countries facing comparable elderly care challenges